Perancangan dan Pengukuran Kinerja Program Inisiatif Perspektif Proses Bisnis Internal - Qurtubi, Qurtubi (Universitas Muhammadiyah Surakarta, 2016)
This paper discusses the design and performance measurement initiative internal business process perspective balanced scorecard, a case study at CV. Fateha Compunet, a company engaged in the trade of computers and official equipments. Research carried out by identifying a problem with the method of observation, formulating business process problems that lead to complaints, collecting primary data and secondary data such as key performance indicators and other supporting data. Survey methods used in the study is the importance analysis. In this technique, the respondents were asked to rank various attributes of a subprogram initiative is based on the degree of importance of each of these attributes. The results showed that based on the monitoring and evaluation of programs key performance indicator value initiatives classified as well so that the target company would potentially be achieved.